Copping Strategies Komunitas Pengamen Jalanan dalam Mempertahankan Keberlangsungan Hidup di Kota Tanjungpinang - Ratih Rahmawaty; Welfiandi Hedy Pratama; Zulmuhaiminuddin Zulmuhaiminuddin; Nikodemus Niko; Emmy Solina (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
musicians from the "KPJ" community in Tanjungpinang City. Utilizing a qualitative descriptive approach, the study collected primary data through observation, interviews, documentary studies, and shared experiences with the "KPJ" community. Secondary data were obtained through academic research and books. The subjects of this study were street musicians in Tanjungpinang City, specifically the KJP community. The findings indicate that the survival strategies of KPJ street musicians involve psychological and economic aspects. Psychological aspects include peer support within the community, while economic aspects involve singing on the streets and relying on contributions from shop to shop